2017
DOI: 10.1111/jai.13250
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between fish size and otolith size of four bathydemersal fish species from the south eastern Arabian Sea, India

Abstract: Summary The objective of this study was to estimate a prey body size from the hard parts (e.g. otoliths) of a fish species frequently found in the guts of predators. Length–weight relationships between otolith size (length, height, weight and aspect ratio) and fish size (total length and weight) were determined for four fish species captured in the Arabian Sea by bottom trawl (2015 survey on‐board FORV Sagar Sampada, 200–300 m depth), off the west coast of India: Psenopsis cyanea, Pterygotrigla hemisticta, Bem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
(37 reference statements)
2
14
0
Order By: Relevance
“…A strong relationship between fish length and otolith size suggests that somatic growth has a major effect on otolith growth (Munk 2012); there are published reports about similar relationships revealed between somatic and otolith growth (Aneesh-Kumar et al 2017;Yilmaz et al 2019). In the present study, linear regressions between fish length and otolith size showed a higher coefficient of determination (r 2 > 0.8) except between fish length and otolith height for L. bata.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…A strong relationship between fish length and otolith size suggests that somatic growth has a major effect on otolith growth (Munk 2012); there are published reports about similar relationships revealed between somatic and otolith growth (Aneesh-Kumar et al 2017;Yilmaz et al 2019). In the present study, linear regressions between fish length and otolith size showed a higher coefficient of determination (r 2 > 0.8) except between fish length and otolith height for L. bata.…”
Section: Discussionsupporting
confidence: 58%
“…There are no published reports available on the relationship between fish length and otolith size and length-weight relationship of otoliths from the target habitat or elsewhere for both fish species. Several researchers have reported that the relationships between fish length and otolith size can be used to back-calculate fish length from otolith size (Harvey et al 2000;Zan et al 2015;Aneesh-Kumar et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations